Electrochemical Assay to Detect Influenza Viruses and Measure Drug Susceptibility - Zhang, Xiaohu (Angew Chem Int Ed Engl, 2015)
We have designed an electrochemical assay to rapidly diagnose influenza viruses. Exposure of a glucose bearing substrate to influenza viruses or its enzyme, Neuraminidase (NA) releases glucose, which was detected amperometrically. We used two methods to detect released glucose. First, we used a standard glucose blood meter to detect two viral NAs and three influenza strains. We also demonstrated drug susceptibility of two antivirals, Zanamivir and Oseltamivir, using the assay. Second, we used disposable test strips to detect nineteen H1N1 and H3N2 influenza strains using this assay in 1 hour. The limit and range of detection of this first generation assay is 10(2) and 10(2)–10(8) plaque forming units (pfu), respectively. Existing, ubiquitous, user friendly glucose meters can be repurposed to detect influenza viruses.